The significant role of Darcy–Forchheimer and thermal radiation on Casson fluid flow subject to stretching surface: A case study of dusty fluid - Ali, Liaqat; Kumar, Pardeep; Poonia, Hemant; Areekara, Sujesh; Apsari, Retna (Modern physics letters. B, Condensed matter physics, statistical physics, applied physics, 2024)
This paper addresses the problem of steady two-dimensional magnetohydrodynamics (MHD) migration of dusty fluid across a stretching sheet with the inclusion of Darcy–Forchheimer porosity and Brownian dispersion. The most significant aspect of the ongoing problem is elaborating the entire context with dusty and fluid phases. The governing partial differential equations (PDEs) are transmuted into non-dimensional ordinary differential equations (ODEs) by implementing similarity transformations. The MATLAB script has used the bvp4c strategy to accumulate a visualization of the computational observations. Also, this study illustrates an assessment of the effects of significant parameters on non-Newtonian fluids and fluids with a dusty phase. It is observed that the thermal boundary layer is enhanced with the increasing strength of the mass concentration of dusty granules ( Γ ν ) and Eckert number (Ec) for both scenarios, while in the case of fluid interaction temperature parameter ( β t ) the scenario is opposite for dusty and fluid phases. Moreover, the heat transfer rate intensifies with the increasing effect of thermal radiation, and magnetic field. The significant variations in the various physical quantities are represented through tabular and graphs.